DISCOURSE ON ‘FEMALE CHASTITY’ AS RATIONALIZATION TO JUSTIFY SEXUAL OFFENSE: Qualitative Case Study of Male Sexual Transgressors - Poerwandari, Elizabeth Kristi; Soekandar, Adriana; Hanum, Lathifah (Jurnal Masyarakat dan Budaya, 2014)
The present qualitative study explores the rationalization of 24(twenty-four) men reported to the police of conducting sexual offense, to justify their sexual offense or transgression. Denials vary from absolute denial, minimization, such as claiming of having mutual consent sex, denial of victim harm, and a rarer phenomenon but apparent in two subjects, a kind of depersonalization. More specific denials relate to gender-based rationalization is prevalent, such as having unharmonious relationship with wife therefore they need other women for sexual outlet, or the girls are not ‘good girl’. Very strong rationalization is related to the discourse on ‘female chastity’ in which offenders justify their behavior as OK since their target subjects are not ‘good girls’, be evidenced by they are not virgin anymore, hang out at night, or have relation with other men. Offenders who are in relationships with their victims need to prove the chastity of their female partner, or felt suspicious and angry about the past relationships of the girls therefore forcing sex or conducting sexual assault. Offender might adopt a ‘professional’, a ‘hero’, a ‘revenger’ as well as a ‘victim’ role. All cannot be separated from the cultural context of Indonesia and are explaining the beliefs of male offenders about men as superior and having authority over women. Keywords: sexual offense; female chastity; cultural context